2018
DOI: 10.5562/cca3353
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Evaluation of Novel Carbazole Based β-diketones and its Pyrazole Derivatives

Abstract: Novel 9-ethyl-9H-carbazole-3-carboxylic acid derivatives including ester, β-diketone and pyrazole were prepared and characterized by FT-IR, 1 H NMR, 13 C NMR and mass spectroscopic techniques. All synthesized compounds evaluated for their in vitro antimicrobial activities against four bacteria (Escherichia coli, Pseudomonas putide, Bacillus subtilis, and Streptococcus lactis) and three fungi (Aspergillus niger, Penicillium sp and Candida albicans). Among the compounds tested, 3a, 3b, 3c, 4a, 4b, 4c, 5a and 5b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Carbazole derivatives present a wide set of biological activities as antimicrobial [72], antiviral [73], antitumoral [74], or anti-inflammatory [75] compounds. For this reason, a set of carbazole-based 1,3-diketones ( 51) have been recently synthesized and evaluated as antimicrobial molecules [76]. 9-Ethyl-9H-carbazole-3-carbaldehyde was oxidized to 9-ethyl-9H-carbazole-3-carboxylic acid 48, which was converted into the corresponding esters by treatment with 2-hydroxyacetophenones (49) in the presence of phosphorous oxychloride and pyridine.…”
Section: Synthesis Of β-Diketones By Claisen Approachmentioning
confidence: 99%
“…Carbazole derivatives present a wide set of biological activities as antimicrobial [72], antiviral [73], antitumoral [74], or anti-inflammatory [75] compounds. For this reason, a set of carbazole-based 1,3-diketones ( 51) have been recently synthesized and evaluated as antimicrobial molecules [76]. 9-Ethyl-9H-carbazole-3-carbaldehyde was oxidized to 9-ethyl-9H-carbazole-3-carboxylic acid 48, which was converted into the corresponding esters by treatment with 2-hydroxyacetophenones (49) in the presence of phosphorous oxychloride and pyridine.…”
Section: Synthesis Of β-Diketones By Claisen Approachmentioning
confidence: 99%
“…Carbazole derivatives have multiple pharmacological activities such as anti-inflammatory [14,32], antibacterial and antifungal [10,25,34], tuberculostatic [33,48,50], antimalarial [26,36], antiviral [7], antioxidant [1,29,45], anticancer [24,39,56] and neuroprotective effects evidenced also in neurodegenerative conditions such as Alzheimer disease [15,35,41,46]. Different research groups assessed the antiproliferative action of carbazoles on different types of tumoral cells.…”
Section: Introductionmentioning
confidence: 99%
“…Structures of the carbazole derivatives reported by Kadnor et al [60,61] DOI: [61] In 2020, Bordei Telehoiu et al reported the synthesis of 6-chloro-9H-carbazol and 1,3,4-oxadiazol scaffolds (23ac and 24a-c) as drawn in Figure 12. This novel adducts were examined against a panel of Gram-negative E. coli (ATCC 25922), P. aeruginosa (ATCC 27853) Gram-positive S. aureus (ATCC 25923), E. faecalis (ATCC 29212) bacteria, as well as the fungal strain C. albicans (ATCC 90029) using the microdilution method in liquid Mueller Hinton medium at a concentrations in the range of 5-0.009 mg/mL.…”
Section: Introductionmentioning
confidence: 99%